A comparative energy analysis of idealized cycles using an ammonia-water mixture for combined power/cooling. (15th December 2022) - Paul Njock, Julbin; Thierry Sosso, Olivier; Stouffs, Pascal; Nzengwa, Robert
Abstract: The Goswami combined power/cooling cycle is an appropriate way to convert energy efficiently. However, in the conventional Goswami cycle (CGC), the refrigeration is not available when the absorber temperature is high. In the present study, a mechanically driven compressor is used to compress the vapors leaving the turbine. This design creates a line independent of the absorber temperature. An idealized cycle approach was used with the assumptions adopted by Goswami. As a result, under the same typical operating conditions, the thermal efficiency of the novel cycle is 27.52% with a net useful effect of 135.2 kW, while the thermal efficiency of CGC is 23.54% with a net useful effect of 99.47 kW. Moreover, at equal total heat input, the working fluid mass flowrate in the novel cycle is less than the CGC. Ultimately, the refrigeration limits highlighted in the CGC were overcome in the novel cycle which allows the availability of refrigeration regardless of the increase in absorber temperature. This advantage, combined with the improved thermal efficiency, suggests a short-to-medium-term payback time of the additional investment cost of the added components and a long-term profitability of the system. Highlights: The vapors recompression leaving the turbine improves the performance of the refrigeration and electricity production. The novel cycle ensures availability of cooling capacity regardless of absorber temperature. The working fluid load of the novel cycle is reduced at equal total heat input compared to the Goswami cycle.